Overexpression of UDP-glucuronosyltransferase and cytochrome P450 enzymes confers resistance to sulfoxaflor in field populations of the aphid, Myzus persicae. (April 2022) - Pym, Adam; Umina, Paul A.; Reidy-Crofts, Jenny; Troczka, Bartlomiej J.; Matthews, Andrew; Gardner, James; Hunt, Benjamin J.; van Rooyen, Anthony R.; Edwards, Owain R.; Bass, Chris
Abstract: The green peach aphid, Myzus persicae, is a highly damaging, globally distributed crop pest that has evolved multiple resistance to numerous insecticides. It is thus imperative that insecticides that are not strongly compromised by pre-existing resistance are carefully managed to maximise their effective life span. Sulfoxaflor is a sulfoximine insecticide that retains efficacy against M. persicae clones that exhibit resistance to older insecticides. In the current study we monitored the efficacy of sulfoxaflor against M. persicae populations collected in Western Australia, following reports of control failures in this region. We identified clones with low (4-23-fold across multiple independent bioassay experiments), but significant, levels of resistance to sulfoxaflor compared with a reference susceptible clone. Furthermore, we demonstrate that sulfoxaflor resistance can persist after many months of culturing in the laboratory in the absence of insecticide exposure. Resistance was not conferred by known mechanisms of resistance to neonicotinoid insecticides, that act on the same target-site as sulfoxaflor, i.e. the R81T mutation or overexpresssion of the P450 gene CYP6CY3 . Rather, transcriptome profiling of multiple resistant and susceptible clones identified the P450 CYP380C40 and the UDP-glucuronosyltransferase UGT344P2 as highly overexpressed (21-76-fold and 6-33-fold respectively) in the resistant clones. Transgenic expression of these genes demonstrated that they confer, low, but significant, levels of resistance to sulfoxaflor in vivo . Taken together, our data reveal the presence of low-level resistance to sulfoxaflor in M. persicae populations in Australia and uncover two novel mechanisms conferring resistance to this compound. The findings and tools generated in this study provide a platform for the development of strategies that aim to slow, prevent or overcome the evolution of more potent resistance to sulfoxaflor. Graphical abstract: Image 1 Highlights: Myzus persicae from Australia exhibit low levels of resistance to sulfoxaflor. Sulfoxaflor resistance is not conferred by overexpression of CYP6CY3. CYP380C40 and UGT344P2 are highly overexpressed in sulfoxaflor resistant M. persicae. CYP380C40 and UGT344P2 confer resistance to sulfoxaflor in vivo.